Pengaruh Konflik Kerja, Stress Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan (Pada PT. Karya Mekar Dewatamali Jombang Jawa Timur) - M. Afiq Fataya Hakim; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of the study was to describe work conflict, work stress and organizational culture and to determine its effect on employee performance simultaneously and partially. This research method uses quantitative methods with this type of research (explanatory research). The sample of this research is the employees of PT. KARYA MEKAR DEWATAMALI using the slovin formula resulted in 61 respondents. Methods of data collection using a questionnaire. The analytical method used in this study is multiple regression analysis with the help of SPSS 16. for windows. The results of this study indicate that: (1) simultaneously there is a significant influence between work conflict, work stress and organizational culture on employee performance at PT. KARYA MEKAR DEWATAMALI while partially (2) work conflict has a significant effect on employee performance (3) work stress does not significantly affect employee performance (4) organizational culture partially affects employee performance at PT. MEKAR DEWATAMALI . Keywords: Work conflict, work stress, organizational culture and employee performance.